A "justice" reading of the trans-national struggle of the people displaced by the Merowe Dam. Issue 2 (1st February 2019) - Zeitoun, Mark; Dirar, Azza; El Moghraby, Asim; Hashim, Mohammad Jalal
ABSTRACT: This paper applies a "justice" lens to the struggle of the people displaced by the Merowe Dam in northern Sudan. Application of distributive, procedural, and representational aspects of justice exposes the dissatisfaction of the affected people with the government's offer and execution of compensation. Consideration of social justice and the utility of norms in trans-national activism brings into sharp focus the difference in interests, and abilities of the many actors involved, and highlights the government's tactics to divide the communities, and the social divisions sown. As the struggle develops, justice claims are seen to change towards less material issues, suggesting that an expanded and dynamic conception of justice is more helpful than narrow or time-bound conceptions. The findings are of relevance to communities facing possible displacement from dams planned nearby, not least of all for the insight provided on the effectiveness of different tactics in the struggle.